الوكالة في الخصومة بين الشريعة والقانون - قصبة, يوسف (University of Eloued جامعة الوادي, 2017)
تناولت هذه الدراسة موضوع الوكالة في الخصومة بين الشريعة والقانون حيت تناول الباحث تاريخها ،وتعريفها من الناحية الشرعية والقانونية ودليل مشروعيتها , ثم تطرقا إلى بيان أركانها وشروطها، والحكمة من تشريعيها، وبيان أحكامها وتكيفها, ثم تناولت حقوق والتزامات الوكالة بالخصومة في الفقه الإسلامي مقارنة بالقانون, وذكر بعض الأحكام المتعلقة بها كأثار الوكالة بالخصومة وأدلة ثبوتها والأمور التي تنقضي بها الوكالة بالخصومة ثم توصل الباحث إلى مجموعة من النتائج والتوصيات من خلال هذه الدراسة . أهمها: - جواز التوكيل بالخصومة في الفقه وأسبقية الشريعة على القانون في هذا المجال. - تفوق وأسبقية الشريعة على القانون . This study dealt with the issue of the Agency in the dispute between the Sharia and the law. The researcher tackled its history, its definition from the point of view of legitimacy and legality, and its legitimacy guide. Then they touched on the statement of its elements and conditions, the wisdom of its legislations, the statement of its provisions, He mentioned some of the provisions related to the effects of the agency on the dispute and evidence of its establishment and the matters that expire by the Agency in the dispute and then the researcher reached a set of conclusions and recommendations through this study. The most important of which: - The power of attorney to dispute in the jurisprudence and the precedence of Sharia on the law in this field. - The superiority and precedence of Shari'a over the law.
مذكرة ماستر تخصص شريعة وقانون
Keywords: الوكالة ، الخصومة ، الشريعة ، القانون .; Agency or Procuratorate ، Rivalry ، Sharia ، Law